2021
DOI: 10.1186/s12939-021-01523-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with seasonal influenza and HPV vaccination uptake among different ethnic groups in Arab and Jewish society in Israel

Abstract: Background Parents in the Arab population of Israel are known to be “pro-vaccination” and vaccinate their children at higher rates than the Jewish population, specifically against human papilloma virus (HPV) and seasonal influenza. Objectives This study seeks to identify and compare variables associated with mothers’ uptake of two vaccinations, influenza and HPV, among different subgroups in Arab and Jewish society in Israel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Heider's balance theory demonstrates a triadic relationship model, where 3 subjects are involved, and individuals seek to maintain a cognitive and emotional balance between 2 or more subjects, so that the ideas are in harmony and free from tension. [30][31][32] With respect to the findings of this study, the individual seeks to maintain a balance between his trust in the Ministry of Health, his trust in the effectiveness and safety of vaccines (which are promoted by the Ministry of Health), and his behavior regarding vaccination. Therefore, a higher level of trust among the groups with pro-vaccination attitudes leads to a higher level of trust in the safety and effectiveness of vaccines (which are promoted by the Ministry of Health), eventually resulting in behavior that reflects vaccination acceptance, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Heider's balance theory demonstrates a triadic relationship model, where 3 subjects are involved, and individuals seek to maintain a cognitive and emotional balance between 2 or more subjects, so that the ideas are in harmony and free from tension. [30][31][32] With respect to the findings of this study, the individual seeks to maintain a balance between his trust in the Ministry of Health, his trust in the effectiveness and safety of vaccines (which are promoted by the Ministry of Health), and his behavior regarding vaccination. Therefore, a higher level of trust among the groups with pro-vaccination attitudes leads to a higher level of trust in the safety and effectiveness of vaccines (which are promoted by the Ministry of Health), eventually resulting in behavior that reflects vaccination acceptance, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, within a few weeks it became clear that while the rate of vaccination in the general population was high, the rate of vaccination in Arab and ultra-Orthodox communities (21% and 13% of the population respectively) was substantially lower [5] . When looking at data regarding other vaccines (Influenza and HPV), it seems that the immunization rate among the Arab community in Israel is even higher than the general population [77] . In contrast, lower rates of childhood vaccinations among some groups within the ultra-Orthodox Jewish community have been described in other studies [78] .…”
Section: Vaccination Programs and Population Preferencesmentioning
confidence: 99%
“…With regard to previous findings, Abramson’s study showed that individuals in Jerusalem who considered themselves religious had a lower rate of taking the influenza vaccine than non-religious individuals [ 14 ]. Another study conducted in Israel indicated that Christian and Muslim groups had a higher likelihood of getting vaccinated than Jewish groups [ 15 ]. Additionally, a study in Vanderbilt University Medical Center (VUMC) revealed that four out of the five most common reasons against vaccination were of a religious nature.…”
Section: Introductionmentioning
confidence: 99%